Climate change and health in urban informal settlements in low- and middle-income countries: a scoping review of health impacts and adaptation strategies - Borg, Frederikke Højgaard; Andersen, Johanne Greibe; Karekezi, Catherine; Yonga, Gerald; Furu, Peter; Kallestrup, Per; Kraef, Christian (Global health action, 2021)
Background: Climate change affects human health with those with the least resources being most vulnerable. However, little is known about the impact of climate change on human health and effective adaptation methods in informal settlements in low- and middle-income countries.Objective: The objective of this scoping review was to identify, characterize, and summarize research evidence on the impact of climate change on human health in informal settlements and the available adaptation methods and interventions.Method: A scoping review was conducted using the Arksey and O’Malley framework. The four bibliographic databases PubMed, Web of Science, Embase, and the Cochrane library were searched. Eligibility criteria were all types of peer-reviewed publications reporting on climate change or related extreme weather events (as defined by the United Nations Framework Convention on Climate Change), informal settlements (as defined by UN-Habitat), low- and middle-income countries (as defined by the World Bank) and immediate human health impacts. Review selection and characterization were performed by two independent reviewers using a predefined form.Results: Out of 1197 studies initially identified, 15 articles were retained. We found nine original research articles, and six reviews, commentaries, and editorials. The articles were reporting on the exposures flooding, temperature changes and perceptions of climate change with health outcomes broadly categorized as mental health, communicable diseases, and non-communicable diseases. Six studies had a geographical focus on Asia, four on Africa, and one on South America, the remaining four articles had no geographical focus. One article investigated an adaptation method for heat exposure. Serval other adaptation methods were proposed, though they were not investigated by the articles in this review.Conclusion: There is a paucity of original research and solid study designs. Further studies are needed to improve the understanding of the impact, the most effective adaptation methods and to inform policy making.
Gesehen am 25.05.2021